The Ottomans and the Balkans : A Discussion of Historiography - Adanir, Fikret; Faroqhi, Suraiya (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
This discussion of historiography concerning the Ottoman Empire should be viewed in the context of our discipline's self-examination, which certainly has been encouraged by recent conflicts in southeastern Europe and the Middle East. Our contributors analyse the fashion in which the historiographies established in various national states have viewed the Ottoman Empire and its legacy. At the same time they discuss the links of twentieth-century historiography with the rich historical tradition of the Ottoman Empire itself, both in its metropolitan and its provincial forms. The struggle against anachronisms born from the nationalist paradigm in history doubtless constitutes the most important common feature of these otherwise very diverse studies.